Fly ash as low cost adsorbent for treatment of effluent of handmade paper industry-Kinetic and modelling studies for direct black dye. (20th January 2016) - Saakshy,; Singh, Kailash; Gupta, A.B.; Sharma, A.K.
Abstract: The handmade paper industry utilizes quantum of dyes for making bright colored handmade paper used for wedding cards, fancy and decorative paper, etc. A study has been conducted on adsorption of direct black dye (used extensively in handmade paper industry to make black colored handmade paper) on fly ash obtained from thermal power plant of Yamuna Nagar. The effluent has been characterized for pH, suspended solids, total solids and chemical oxygen demand. The batch and column studies have been conducted on the adsorption of direct black dye solution of different concentrations on fly ash at varying pH, dosage of fly ash, temperature, contact time, particle size fractions of fly ash and initial concentration of dye solution. In batch studies, it was observed that the experimental data fit well with Langmuir adsorption isotherm in comparison to Freundlich and Temkin isotherms. The maximum adsorption capacity of 76.33 mg/g was achieved at 318 K in batch studies. The column experimental data fitted well to Yoon–Nelson model and Thomas model in comparison to Bohart–Adams model. The maximum adsorption capacity of 45.54 mg/g in column study was obtained for 2.4 cm bed height, 150 ppm inlet concentration and 1.6 mL/min flow rate of dye solution. The calculations of thermodynamic parameters indicate that the adsorption of black dye on fly ash is spontaneous and endothermic in nature and follows first order kinetics with rate constant of 0.201 min −1 . It has been found that fly ash is a potential low cost adsorbent to treat effluent of handmade paper industry. The exhausted fly ash can be further reused as filler in paper making and hence can offer a viable closed loop solution in curbing pollution from this predominantly small sector industry. Highlights: First report on fly ash as a low cost solution for handmade paper industry. Exhausted fly ash reused as filler in handmade paper making. Reuse of exhausted fly ash offers close loop solution.